The effect of irrigation solutions and file types on the accuracy of electronic apex locator: an in vitro study - Nguyen, Thi Thuy Duong; Hoang, Trong Danh; Le, Thi Khanh Huyen (Tạp chí Y Dược Huế, 2024)
Background: To achieve success in endodontic treatment, working length can be accurately determined using an electronic apex locator. However, the accuracy of the apex locator is not always stable across different root canal environments. This study aims to evaluate the accuracy of the Apex ID, 4th generation of apex locator, under various irrigation solutioans and types of measuring files. Materials and methods: a total of 40 extracted lower premolars were instrumented using size 15-30 K-files. The teeth were then divided randomly into 4 groups of 10 teeth each, to evaluate the working length by the Apex ID apex locator in 4 different conditions. Four irrigation solutions, two concentrations of irrigation solution, six K-file sizes, and two file types were used to assess the accuracy of the Apex ID. Result: This study showed no statistically significant difference in working length and deviation from the actual canal length values between different measurement conditions. However, the accuracy of the Apex ID varied among different irrigation solutions, file sizes, and file materials. NaOCl and NaCl solution, K-file size 25-30 with the Apex ID showed 100% accuracy. Conclusion: The accuracy of the Apex ID apex locator varies under different conditions of measuring the working length. Using the NaOCl solution and selecting file sizes close to the size of the root canal is recommended to achieve high accuracy.